2020
DOI: 10.1177/1071100720942173
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Magnetic Resonance Imaging Outcomes of Microfracture Plus Chitosan/Blood Implant vs Microfracture for Osteochondral Lesions of the Talus

Abstract: Background: The aim of this study was to compare the clinical and magnetic resonance imaging (MRI) outcomes of arthroscopic microfracture (MF) plus chitosan-glycerol phosphate/blood implant and MF alone for the treatment of the osteochondral lesions of the talus (OCLTs). Methods: Patients who underwent either MF plus chitosan (group 1, n = 32) or MF alone (group 2, n = 31) between 2015 and 2019 in 2 separate time periods were retrospectively analyzed. Visual analog scale (VAS) score and American Orthopaedic Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“… a Significantly different from osteo(chondral) autograft transplantation therapies ( Q = 7.55, P = 0.0060) and metal implants ( Q = 5.27, P = 0.0217). 43,52,59,61 -63,66,81,92,93,109,113,117,121,123,125,131,135,141,143,146,149,150,153,158,164,165,167,168,171,173,176,177,179 -183,187,190,192,195 -200,202,204 -206 b Significantly different from metal implants ( Q = 3.86, P = 0.0493). 11,42,53,56,59,116,118,137,170,…”
Section: Resultsmentioning
confidence: 99%
“… a Significantly different from osteo(chondral) autograft transplantation therapies ( Q = 7.55, P = 0.0060) and metal implants ( Q = 5.27, P = 0.0217). 43,52,59,61 -63,66,81,92,93,109,113,117,121,123,125,131,135,141,143,146,149,150,153,158,164,165,167,168,171,173,176,177,179 -183,187,190,192,195 -200,202,204 -206 b Significantly different from metal implants ( Q = 3.86, P = 0.0493). 11,42,53,56,59,116,118,137,170,…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in 13 studies that met the eligibility criteria and therefore, included in the systematic review (Fig. 1) [1, 2, 6, 8, 12, 14, 15, 19–21, 26, 27, 31]. The interobserver agreement rate of the included studies was 100%.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative clinical studies with unique treatment arms were distinct in four studies [2, 6, 21, 27]. The studies investigated BMS versus AMIC [2], BMS versus BMS + chitosan‐glycerol phosphate/blood implant [6], BMS versus BMS + atelocollagen [21], and BMS versus CBMA alone [27]. The total number of OLTs as protocol of all treatment arms was 178.…”
Section: Resultsmentioning
confidence: 99%
“…There was no difference in patient-reported outcomes, but MRI scores using the Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) scale were significantly higher in the biologic repair group. Camurcu et al 41 found near-identical negative clinical results in a similar retrospective comparison of microfracture alone and microfracture plus chitosan-glycerol phosphate mixed with peripheral blood. Park et al 42 found only modest degradation in patient-reported outcomes at the 10-year mark in a group of 189 patients who initially responded to microfracture.…”
Section: Athletic Injuriesmentioning
confidence: 89%